2014
DOI: 10.1016/j.neuro.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of cisplatin-induced experimental peripheral neuropathy by a small molecule targeting p75NTR

Abstract: Cisplatin is an effective and widely used first-line chemotherapeutic drug for treating cancers. However, many patients sustain cisplatin-induced peripheral neuropathy (CIPN), often leading to a reduction in drug dosages or complete cessation of treatment altogether. Therefore, it is important to understand cisplatin mechanisms in peripheral nerve tissue mediating its toxicity and identify signaling pathways for potential intervention. Rho GTPase activation is increased following trauma in several models of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…7a ). In contrast, the level of phosphorylated RhoA (p-RhoA, a marker of the inactive form of RhoA) 32 was significantly increased in BMSCs co-cultured with RAOECs (Fig. 7b ), indicating that RhoA signaling was inhibited when BMSCs were co-cultured with RAOECs.…”
Section: Resultsmentioning
confidence: 98%
“…7a ). In contrast, the level of phosphorylated RhoA (p-RhoA, a marker of the inactive form of RhoA) 32 was significantly increased in BMSCs co-cultured with RAOECs (Fig. 7b ), indicating that RhoA signaling was inhibited when BMSCs were co-cultured with RAOECs.…”
Section: Resultsmentioning
confidence: 98%
“…Suppression of small GTPase RhoA signaling, either through inhibition of its upstream p75 NTR or the downstream effector Rho kinase/p160 ROCK , reversed and prevented experimental CIPN in non-tumor-bearing mice (8,23). This study demonstrated, for the first time, that Y-27632 had dual therapeutic effects on tumor suppression and peripheral neuroprotection in an immunocompetent, tumor-bearing CIPN mouse model.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, increased activity of RhoA, a member of Rho family small GTPases, has been observed in a variety of neuronal injuries (5). LM11A-31, a ligand mimetic of p75 neurotrophin receptor (p75 NTR ) that is upstream of the RhoA signaling pathway (6,7), could partially protect peripheral nerves from being damaged by cisplatin (8). The notion of RhoA involvement in CIPN was further supported because Y-27632, a selective inhibitor of Rho kinase/ p160 ROCK directly downstream of RhoA (9), reversed the neurodegeneration caused by cisplatin (9).…”
Section: Introductionmentioning
confidence: 99%
“…For CIPN, rhNGF improved results of nerve conduction study on cisplatin neurotoxicity in rodents [ 14 , 17 ]. In addition, p53 pan-neurotrophin receptor ( p 75 NTR ), one of NGF receptors, agonist also decreased CIPN incidence [ 35 ]. However, well-designed human trial has not been performed, probably because of uncertainty.…”
Section: Discussionmentioning
confidence: 99%